Sequestration of Carbon and Oxygen Production in Upper Stands in The Arboretum of PT Arutmin Indonesia NPLCT - Muhana, Muriyana; Mendra, Yogi Swara Putra; Bahtiar, Bahtiar (International Journal of Social Service and Research, 2024)
This study aims to determine biomass, carbon, carbon uptake, and oxygen production in the arboretum of PT. Arutmin Indonesia-NPLCT. The methods used are purposive sampling and allometrics. The plot size useda is 20 m  20 m with 12 plots measured. The area of the arboretum is 5.05 ha. Carbon stock measurement is done by multiplying biomass by a conversion rate of 0.47 (47%) while carbon dioxide (CO2) sequestration is calculated by multiplying the average annual biomass growth by the conversion rate of 1.4667 obtained from the photosynthesis equation and oxygen production is measured based on conversion from carbon yield. Based on the results of the study, it showed that the biomass content of stands in the arboretum was 1,067.32 tons, carbon stocks were 501.64 tons, carbon dioxide (CO2) absorption was 1,565.45 tons, and oxygen production was 1,337.71 tons.